(untitled) (Transactions of the Association of European Schools of Planning, 2017)
Sustainable land use needs a manageable nexus of knowledge from planning practice, policy makers, the private economy, and civic society, as well as from scientific research. This is mutually dependent on the communicative and collaborative turn in spatial planning as well as by transdisciplinary research approaches. This paper offers an approach how to organise knowledge management and co-production of knowledge in the context of complex land use decisions. Therefore, a prototype of an internet-based knowledge platform is introduced based on a theoretical reflection of concepts for integrated information and knowledge management, as well as on practical experiences derived from a German case study. We conclude that sustainable land use requires Planning Support Systems (PSS) that combine transdisciplinary perspectives in order to co-produce robust knowledge. This also implies a transdisciplinary design of PSS. Challenges of implementation are discussed and further research is specified.